Postharvest evaluation of Colletotrichum gloeosporiodes f. sp. manihotis on cassava genotypes - Fokunang, C.N.; Dixon, A. (2006)
The aim of this study was to evaluate the post-harvest survival of Colletotrichum gloeosporioides f. sp. manihotis on infected cassava materials. Infected stem cuttings from 5 cassava cultivars 88/01084, 88/01983, 91/00395, 91/00317 and 91/00052, incubated at 25±2°C for 8 months, showed a significant decrease in fungal survival amongst the cassava cultivars. At 8 months incubation fungal recovery was lowest below 10% among the infected cultivars. Cassava stakes, stored at humid conditions under tree shades for 16 months, showed a gradual decrease in fungal survival up to the 10th month, after which survival peaked again from the 12th up to the 16th month of storage. Survival of the fungus on soil significantly reduced with incubation time and at the 6th month of sampling, there was no recovery recorded for all the soils from the field plot sites. Burial of infected materials for 150 days below 20-30 cm depth significantly reduced the survival of C. gloeosporioides f. sp. manihotis on infected materials. Burial at 30 cm depth for 150 days completely eradicated the fungus on the infected cuttings. These studies have shown that C. gloeosporioides f. sp. manihotis could survive on infected cuttings for more than 8 months, but less likely to survive in soil for up to 4 months. The potential of high cassava anthracnose disease transmission in cassava planting materials during storage is also reported.